PENGARUH LATIHAN HIP ROTATION TERHADAP KELINCAHAN TIM BOLA BASKET SMP NEGERI 6 SIAK HULU KABUPATEN KAMPAR - Fitrah Hidayat; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that their agility is still not optimal, it can be seen from the slowness of students in making changes when changing direction in finding position, difficult to pass the opponent when mastering the ball, and difficult to follow or keep the opponent while defending. The purpose of this research was to determine the effect of hip rotation training on the agility of the basketball team at SMP Negeri 6 Siak Hulu Kabupaten Kampar. The population and sample in this research were the basketball team of SMP Negeri 6 Siak Hulu Kabupaten Kampar, amounting to 10 people. The instruments used to collect data are pre test and post test illinois agility run. The data analysis technique used is the t test. The results showed that the average value of student agility during the post test was 19.56 when compared to the average agility of students when pre-test was 20.22. So the verification is shown by the significant value of t arithmetic = 10,408> value of t table = 1,833. So with this there is a significant influence from hip rotation training on the agility of the basketball team at SMP Negeri 6 Siak Hulu Kabupaten Kampar.Key Words: hip rotation exercise, agility